Effects of social context on 5-year-olds’ performance on a flexibility task. - Ng, Hui Qun. (2010)
The impact of social contexts on 5-year-old’s flexibility was examined. Children’s flexibility was measured with a block sorting task where they sorted 12 blocks using different dimensions without being told which dimensions to sort by. Scoring was based on the number of accurate sorts and the complexity of the sorting dimension. Children were randomly assigned to three social context conditions: playing alone, playing with a passive cooperator, and playing with a competitor. Results have shown that children differed significantly across the three conditions for the number of accurate sorts. Particularly, the children under the competition condition sorted significantly more blocks than the children under the individual condition. No facilitation effect was observed in terms of engagement of complex dimensions. These suggest that social context can influence preschoolers’ flexibility.